Illness perception of tuberculosis (TB) and health seeking practice among urban slum residents of Bangladesh: a qualitative study - Bam, Kiran; Prasad Bhatt, Lokesh; Thapa, Rajshree; Karimjee Dossajee, Hussein; Raj Angdembe, Mirak (© 2014 BioMed Central Ltd., 2017)
This article was published in BMC Research Notes [© 2014 BioMed Central Ltd.] and the definite version is available at: http://bmcresnotes.biomedcentral.com/articles/10.1186/1756-0500-7-572